Improving MSME Competitiveness Through Knowledge Management and Human Resource Development: A Case Study of MSMEs in Sorong City, Southwest Papua Province - Ahmad Jamil; Evi Mufrihah Zain; Retno Dewi Wijiastuti; Febry Jein Andjar; Ditha Vanneza Amanupunyo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine whether there is a relationship between knowledge management and human resource development on the competitiveness of MSMEs (Micro, Small, and Medium Enterprises) in Sorong City, Southwest Papua. Specifically, this study seeks to demonstrate that: there is a relationship between knowledge management and the competitiveness of MSMEs; and there is a relationship between human resource development and the competitiveness of MSMEs in Sorong City, Southwest Papua. The research was conducted in Sorong City, Southwest Papua, involving 378 MSMEs as the sample. The method used in this study is quantitative research with a survey approach for data collection. The results of the analysis indicate that there is a positive but not significant relationship between knowledge management and the competitiveness of MSMEs in Sorong City, Southwest Papua. Furthermore, there is a positive and significant relationship between human resource development and the competitiveness of MSMEs in Sorong City, Southwest Papua Province.